Behavioral Intention to Re-Use Online Learning Platform - Akram Harmoni Wiardi; Trisna Murni; Rina Sutia Hayu; Effed Darta Hadi (Universitas Nusa Cendana, 2022)
The Technology Acceptance Model (TAM) is a model used to predict user acceptance of information systems based on perceived usefulness and perceived ease of use. If the user sees the benefits and ease of using the information system, it will cause the user's actions to accept the use of the information system. This study aims to examine the effect of IT system quality and perceived usefulness on the intention to reuse online learning applications. This research analyze the measurement of perceptions of the quality of the IT system used by respondents in the scope of online learning. We operate a survey method, the respondents in this reseacrh were students and teaching staff users of online learning applications. Respondents, most of whom are students in Sumatra, are interested or have the intention of reusing online learning applications if there is a good information quality factor and more benefits from online applications. The perceived usefulness construct plays a full role as a mediating variable of the relationship between information quality and intention to reuse online learning applications.